Effects of low-frequency vibration on mechanical properties and microstructure of aluminium eutectics - Baybalı, Süheyl. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
In this study, the effects of low-frequency vibration on mechanical properties and microstructure of aluminium eutectics, Al-% 33 Cu, Al-% 12.6 Si, Al-% 5.7 Ni, were investigated. A brief rewiev of the eutectic solidifying structures and the theory of the applied low-frequency vibration were / presented to-gether with the effects of low-frequency vibration on lamellar, dendritic solidifying structures and on pure metals, solid solutions and eutectics. In the experimental work, unvibrated and vibrated aluminium eutectic ingot castings weie treated to differant rate of solidification and then the mechanical properties were measured with tensile and hardness. testing. The resulting microstructure was investigated in detail to reveal the effects produced by variable solidification rate and low-frequency vibration. Finally, the obtained ultimate tensile strength and Vickers hardness data have been correlated to the increasing mould temperature, casting temperature and vibration amplitude.
Keywords: Eutectic alloys.; Aluminum alloys.; Vibration.